Influence of chemotherapy on postural control and quality of life in women with gynaecological cancer: a protocol of a prospective observational study - Joseph Gligorov; Christophe Combescure; Anne-Violette Bruyneel; Thibaud Koessler; Aline Reinmann; Serge Mesure; Alexandre Bodmer (BMJ Open, 2022)
Introduction Chemotherapy-induced peripheral neuropathy is a frequent side effect of some chemotherapies that can cause postural control disorders and has a serious impact on quality of life (QoL). An enhanced understanding of postural control dysfunction could help build a systematic and accurate assessment as well as specific exercises to limit the impact on QoL. This study aims to assess the influence of chemotherapy on postural control and the QoL for women with gynaecological cancer.Methods and analysis This prospective observational study will include 37 participants with cancer treated using neurotoxic chemotherapy. Their postural control in various conditions (rigid and foam surfaces, eyes open and closed, with and without tendon vibration, and dual tasks), limits of stability, QoL and modified Total Neuropathy Score will be assessed. A linear mixed model will compare postural control pre-chemotherapy and post-chemotherapy.Ethics and dissemination This study was approved by an ethical review board in Geneva (CCER-2020-01639). The study findings will be disseminated through conference presentations and publications in peer-reviewed journals.Trial registration number NCT04692168.